SIRT1 / NF-κB pathway on neuronal apoptosis in rats with ischemic stroke: SIRT1/NF-κB pathway on neuronal apoptosis - Gao, Hongli; Yang, Lingling; Shao, YiShun (Cellular and Molecular Biology, 2022)
Recent studies have shown that neuronal apoptosis is one of the important mechanisms leading to cerebral ischemic injury. SIRT1/NF-κB is a carrier of protein units in the body, participates in the synthesis of DNA, RNA and important neurotransmitters in the brain, and is an important nutrient necessary to maintain the normal growth and development of the nervous system and the normal function of cells. This article aims to study the effect of the SIRT1/NF-κB pathway on neuronal apoptosis in rats with ischemic stroke. Rats were divided into sham operation group, model group, SIRT1/NF-κB group, each group was given intragastric administration at different doses 3 days before the operation and after the operation, and brain tissue was taken at 24, 48, 72, 96 h after operation HE staining, TTC staining and dynamic changes of SIRT1/NF-κB expression were measured. The results of the experiment showed that the result of Nao Xintong was low, and the SIRT1/NF-κB group could reduce the volume of cerebral infarction in rats (P <0.05), and reduce the expression of SIRT1/NF-κB positive cells. The experimental results show that Naoxintong SIRT1/NF-κB has a protective effect on neuronal apoptosis after focal cerebral ischemia-reperfusion in rats.